Growth Promoting Endophytic Bacteria from Zingiber officinale - Anwer Sharook MD,; Darsha S, (International Journal of Scientific Research in Science and Technology, 2025)
Endophytic bacteria are those which colonize the interior tissues of plants without causing any adverse effect. The mutualistic association of endophytes with plants enables the plant to manage diverse stress conditions and they provide several plant growth promoting properties to the plants. This paper explores the isolation and characterization of plant growth-promoting endophytic bacteria from the rhizome of Zingiber officinale. This paper aims to contribute to the understanding of the endophytic bacterial community associated with ginger plants and their potential applications in agriculture. The findings may have implications for sustainable crop production practices, including the development of biocontrol agents against plant pathogens and the promotion of plant growth in agricultural systems.
Keywords: Zingiber officinale; Endophytic bacteria